Magnetic particle imaging angiography of the femoral artery in a human cadaveric perfusion model - Viktor Hartung; Philipp Gruschwitz; Anne Marie Augustin; Jan-Peter Grunz; Florian Kleefeldt; Dominik Peter; Süleyman Ergün; Johanna Günther; Teresa Reichl; Thomas Kampf; Martin Andreas Rückert; Stefan Herz; et al. (Communications Medicine)
Abstract Background Magnetic particle imaging (MPI) allows for radiation-free visualization of tracers without background signal. With the first human-sized interventional MPI scanner being recently developed, the aim of the present study was to test its performance for guiding of endovascular procedures in a realistic perfusion model. Methods Three fresh-frozen cadaveric legs were prepared to establish continuous circulation in the superficial femoral artery via introducer sheaths in the inguinal and infragenicular region. To facilitate vessel visualization, a mixture of a MPI tracer (Resotran® or Perimag®) and X-ray contrast agent was injected under continuous extracorporeal perfusion and imaged simultaneously with MPI angiography and digital subtraction angiography (DSA) as reference. Results The MPI scanner integrates seamlessly into the standard operating procedures in the angiography suite and simultaneous imaging with DSA and MPI is feasible. The MPI scanner detects a tracer bolus of 2 ml Perimag® or 1.5 ml Resotran®. Imaging results are consistent and reproducible in three cadaveric leg phantoms. Conclusion This study demonstrates, that the recently developed human-sized MPI scanner facilitates reliable radiation-free image guidance for peripheral vascular interventions in the superficial femoral artery with a tracer approved for use in humans.